2021
DOI: 10.1038/s41598-021-83938-y
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin promotes oligodendrocyte differentiation and their protection against TNF-α through the activation of the nuclear receptor PPAR-γ

Abstract: Curcumin is a compound found in the rhizome of Curcuma longa (turmeric) with a large repertoire of pharmacological properties, including anti-inflammatory and neuroprotective activities. The current study aims to assess the effects of this natural compound on oligodendrocyte progenitor (OP) differentiation, particularly in inflammatory conditions. We found that curcumin can promote the differentiation of OPs and to counteract the maturation arrest of OPs induced by TNF-α by a mechanism involving PPAR-γ (peroxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 53 publications
1
25
0
2
Order By: Relevance
“…A small set of molecules has been previously synthesized by combining the functional moieties of curcumin and diallyl sulfide: curcumin is known to activate the NRF2 and PPAR-γ pathways [25,37,38], and diallyl sulfide is known to induce the expression of antioxidant phase II enzymes by activating the NRF2 pathway [24,39] (Figure 1). Among these hybrids, compound 1 was found to be one of the most active in modulating the activation of NRF2 pathway [24,25].…”
Section: Effects Of Hybrids On the Nrf2/are Axismentioning
confidence: 99%
See 1 more Smart Citation
“…A small set of molecules has been previously synthesized by combining the functional moieties of curcumin and diallyl sulfide: curcumin is known to activate the NRF2 and PPAR-γ pathways [25,37,38], and diallyl sulfide is known to induce the expression of antioxidant phase II enzymes by activating the NRF2 pathway [24,39] (Figure 1). Among these hybrids, compound 1 was found to be one of the most active in modulating the activation of NRF2 pathway [24,25].…”
Section: Effects Of Hybrids On the Nrf2/are Axismentioning
confidence: 99%
“…Curcumin is known to induce both the PPAR-γ and NRF2 pathways. As pio, curcumin induces cell differentiation and protection from TNF-γ damage through activation of the PPAR-γ pathway in OPs [38]. On the other hand, curcumin induces phase II enzymes and protects from oxidative and mitochondrial stress by activating NRF2 in different cell types [57,58].…”
Section: Effects Of Hybrids On the Nrf2/are Axismentioning
confidence: 99%
“…Cumulative evidence also indicate an interplay between ROS and inflammation in noise trauma, ototoxicity and age-related hearing loss [ 5 , 10 , 14 , 47 , 48 , 49 , 50 , 51 , 52 ]. Moreover, several studies have demonstrated PPAR ability to inhibit the expression of inflammatory markers and signaling pathways, such as cytokines, metalloproteases and acute phase proteins [ 53 , 54 , 55 , 56 , 57 ]. In order to establish a cause-effect relationship among PPAR down-regulation, increased oxidative stress and increased inflammatory markers in cochlear noise-induced injury, we used both antioxidant (Q-ter) and anti-inflammatory (Anakinra) treatments for investigating the effect of blocking oxidative stress or direct inhibiting inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…This observation could suggest that under stress conditions, cells may become more sensitive to differentiating stimuli. Similarly, other PPAR-γ agonists, such as PIO, DHA or curcumin, were more effective in promoting OP differentiation under inflammatory stress, induced by the inflammatory cytokine TNF-α [21,52,53]. In a general view, the capability to respond to stress by entering a differentiation status might be considered a general feature of cells in the early stages of their development, as OPs are.…”
Section: Discussionmentioning
confidence: 99%